Fundamental Analysis and Intrinsic Value of PT Semen Indonesia (Persero) Tbk (SMGR) and PT Indocement Tunggal Prakarsa Tbk (INTP) as Leading Companies in the Cement Industry in Indonesia - Astuti, Niken Yulia (PT. Batari Edu Calya, 2023)
The Indonesia Stock Exchange categorizes companies into several business sectors. One of the sub sectors on the IDX is the cement sub sector. The author is interested in conducting research related to stock valuation in determining the intrinsic value of shares and measuring financial performance at PT Semen Indonesia (Persero) Tbk. (SMGR) and PT Indocement Tunggal Prakarsa Tbk. (INTP) as the leading in the cement industry in Indonesia and its relation to investment decision-making strategies. To reduce the risk in investing, investors must be able to analyze the company's financial statements, including its financial performance. The financial ratios used in this study are ROE (Return On Equity), EPS (Earning Per Share), DPS (Dividend Per Share), DPR (Dividend Payout Ratio), and PER (Price Earning Ratio). In addition, researchers also use SWOT analysis to find out the strategies that should be applied by the two companies. Based on the results of fundamental analysis and intrinsic value, it is concluded that in terms of financial ratios in the 2020-2022 period, INTP is slightly better than SMGR. However, based on intrinsic value at June 2023, SMGR is better than INTP because SMGR still tends to be undervalued when compared to INTP which tends to be highly overvalued.